Customer Developing In Using the Islamic Banking Product at Bank Syariah Mandiri Tbk, Tegal Branch - Makmur Sujarwo; Adi Inayah Sari (Benefit: Jurnal Manajemen dan Bisnis, 2017)
This research is aimed to find out the influences of perception, attitude, motivation, religiousness and learning towards the customer's decision in choosing the islamic banking product. This research sample is the customer's Bank Syariah Mandiri Tegal. The total samples are 105 people from Tegal, Tegal Regency and Brebes Regency. The respondent's answers towards closed questions related to the studied variable in this research, then were analyzed by using double linear regression test, while the answers to the opened questions were analyzed qualitatively.The analysis result showed that the motivation and learning variables give positive and significant affect towards the customer's decision in choosing islamic banking product. Meanwhile, the perception, attitude, and religiousness variables do not give any affect towards the customer's decision.